SOTO KWALI SOLO MBOK DARMI'S FAMILY BUSINESS STRATEGY IN INCREASING SALES IN SEMER 50, KEROBOKAN, KUTA, BADUNG REGENCY, BALI - I Wayan Ruspendi Junaedi (International Journal of Family Business Practices, 2021)
Soto Kwali Solo Mbok Darmi is a family business located on Jl. Semer No 50 Kerobokan Village, Kuta District, Bali Province, established in 2016. The research problem is “What is the strategy used by the management of Soto Kwali Solo Mbok Darmi in increasing its sales?” The purpose of this research is to determine the strategies used by the management of Soto Kwali Solo Mbok Darmi in increasing sales. The research method used is a qualitative research method, by conducting observations, interviews with owners and managers of Soto Kwali Solo Mbok Darmi, and documentation. The findings and analysis are that in the process of making and presenting Soto Kwali Solo Mbok Darmi, they were very concerned with cleanliness, employee hospitality, food delicacy, and ethics and consumer culture so that they have many consumers. Initially they only use conventional marketing strategies. However, eventually it changed, and the strategy used in increasing their sales was to provide training to all employees in management and marketing management and the use of technology related to GoFood and Grab. This business is sufficiently developed to its maximum potential so that its sales turnover is quite interesting. In the end, they were able to increase sales of the business. The marketing strategy is getting better because it uses a marketing strategy using Social Media through Facebook, Instagram, and WhatsApp, as well as GoFood and GrabFood. The family business of Soto Kwali Solo Mbok Darmi can develop, sales turnover is increasing, and provides inspiration to the community to become entrepreneurs so as to improve the welfare of the business.Keywords: Menu, Strategy, Soto Kwali Solo Mbok Darmi Family Business, Marketing and Sales.